2015
DOI: 10.1590/1807-3107bor-2015.vol29.0104
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial action of sodium hypochlorite and castor oil solutions for denture cleaning – in vitro evaluation

Abstract: The objective of this in vitro study was to evaluate the antimicrobial action of sodium hypochlorite (0.25% and 0.50%) and 10% castor oil solutions against specific microorganisms, by counting Colony Forming Units (CFU) of clinically important bacteria and Candida species. Acrylic resin specimens (n = 320; Lucitone 550) were obtained from square metal matrices (10 x 10 x 2 mm), sterilized by microwave (650W, for 6 minutes) and contaminated by Staphylococcus aureus, Pseudomonas aeruginosa, Candida albicans, Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 25 publications
2
46
0
13
Order By: Relevance
“…This result is important when considered with the results of studies showing that 0.25% sodium hypochlorite is effective in reducing CFU and removing biofilm, suggesting its possible indication as an alternative to prosthesis hygiene. It should be noted, however, that other important properties of the resin such as hardness, color, and flexural strength must be considered when exposed to immersion in sodium hypochlorite at 0.25%.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This result is important when considered with the results of studies showing that 0.25% sodium hypochlorite is effective in reducing CFU and removing biofilm, suggesting its possible indication as an alternative to prosthesis hygiene. It should be noted, however, that other important properties of the resin such as hardness, color, and flexural strength must be considered when exposed to immersion in sodium hypochlorite at 0.25%.…”
Section: Discussionmentioning
confidence: 89%
“…However, only a few studies on the efficacy of R. communis solutions as complete denture cleansers have been conducted . Therefore, an experimental solution of 10% R. communis and 0.25% NaOCl solution were prepared as denture cleansers …”
mentioning
confidence: 99%
“…Correct denture hygiene is essential to reduce or eliminate pathogens 15 , 22 , 23 and establish an environment suitable for the growth of beneficial oral microbiota. Studies have shown that a combination of mechanical and chemical cleaning is efficient in the maintenance of denture hygiene 7 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…NaOCl solution that also used in the present study in the concentration of 5%, dissolves mucin, organic substances and shows antimicrobial activity by the action of hydroxyl ions and chloramination 20,29) . Several studies have reported satisfactory results for the antimicrobial activitiy of NaOCl solutions with different concentrations on denture base materials [30][31][32] . However, NaOCl has some disadvantages on denture base materials such as discoloration and an increase in surface roughness, depending on the concentration and immersion time 17,[33][34][35] .…”
Section: Discussionmentioning
confidence: 99%